Electromagnetic counterparts of gravitational-wave signals. Issue 4 (1st August 2021) - Nuttall, Laura K; Berry, Christopher P L
Abstract : Laura Nuttall and Christopher Berry review the potential of multimessenger astronomy with gravitational-wave observations Abstract: Laura Nuttall and Christopher Berry review the potential of multimessenger astronomy with gravitational-wave observations